Acupuncture Anxiolytic Effects on Physiological and Psychological Assessments for a Clinical Trial. (4th April 2016) - Shayestehfar, Monir; Seif-Barghi, Tohid; Zarei, Sahar; Mehran, Amir
Abstract : In a randomized controlled trial we examined the effect of acupuncture on anxiety of the adolescent football players prior to the competition using psychological and physiological markers. A total of 45 athletes were equally allocated to either acupuncture group, sham group, or wait-list control group. Thereafter, all participants were asked to complete an anxiety questionnaire before and after the intervention. Their heart rate and skin conductance were also examined before and after the intervention. The results of ANOVA on posttest scores showed that acupuncture had a significant effect on cognitive anxiety (p = 0 . 001 ) and somatic anxiety (p < 0 . 001 ) but not on self-confidence (p > 0.05 ). Furthermore, the results showed that acupuncture significantly decreased the skin conductance in acupuncture group compared to sham group (p = 0 . 006 ) and wait-list control group (p < 0 . 001 ). In conclusion, the results suggested that acupuncture has the capacity to decrease cognitive anxiety and somatic anxiety prior to competition in adolescent athletes, while this was accompanied by significant physiological changes. This trial is registered withIRCT138904074264N1 (IRCT is a Primary Registry in the WHO Registry Network).